The analysis and design of deep-sea lighting field based on spectral transfer function - Quan, Xiangqian; Wei, Yucong; Liu, Kaibin; Li, Bo (Frontiers in Marine Science, 2022)
As one of the real-time and in situ observation technologies in deep-sea exploration, the deep-sea optical imaging system is widely used on the deep-sea working platforms. As a result of the attenuation of light in water, the deep-sea optical imaging system needs an active lighting system to provide the light source. However, due to the nonlinearity of light attenuation in spatial dimension and spectral dimension, the deep-sea lighting differs from terrestrial lighting. The conventional deep-sea lighting design usually ignores the spectral transmission process. In order to quantitatively analyze and design deep-sea lighting system, we proposed a precise deep-sea lighting field simulation model and design method based on spectral transfer function. Firstly, with the analysis of deep-sea lighting-imaging process, the spectral transfer function in lighting field was analyzed and the deep-sea lighting model was built. Then, the platform used to study light attenuation was set up and the attenuation characteristics of light in water were derived. Moreover, the deep-sea lighting field simulation model was built with the computer program. Finally, the experiment platform for testing the underwater lighting field was set up in test pool. The experimental results show that the deep-sea lighting field computational model is accurate, and the optimal deep-sea lighting system design was proposed. This study provides the theoretical basis and experimental data for the design of a deep-sea lighting system.